IMPLEMENTASI KEBIJAKAN PEMBENTUKAN PERANGKAT DAERAH PADA PEMERINTAH KOTA SINGKAWANG - Abdul Rahman; Riani Bakri (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2017)
The formation of regional devices based on the potential of region has set to the affairs of concurrent government and the elements of support in the certainty of PP No. 18/2017 about of regional devices. The policy implementation The formation of regional devices of Singkawang City Govermment from the communication aspect, community parcipation with compositation of regional devices have to good run. But need to improvement the human resources is not smooth and own technical capability. The ASOCA approach results of three strategy of fhe formation of regional devices, including: the positation admissing with merit system; raising of managerial skill; and raising of supervision, creation and coordinstion based culture for upgrade of aparatus performance.